Analisis Minat Muzakki Membayar Zakat di Badan Amil Zakat Nasional (Baznas) Kota Semarang - Rosida Dwi Ayuningtyas; Risti Lia Sari (Universitas Wahid Hasyim, 2020)
The purpose of this study was to analyze the interest of muzakki paying zakat in the Semarang baznas. The research method used is qualitative quantitative by means of distributing questionnaires. The sample used was 50 respondents. The results of this study resulted that from the independent variables (service quality, religiosity and accountability) affecting the interest of muzakki to pay zakat in Baznas Semarang only 69% of service quality, while for religiosity and accountability there was no partial effect on the interest of muzakki paying zakat in the baznas Semarang city. For the determination value of 41% which means that the independent variable variation model is only able to provide the information needed to predict the interest in paying zakat in the city of Semarang baznas by 41%. Keywords :Accountability, Baznas, Interest of Muzakki Paying Zakat, Religiosity, Service Quality